Pengaruh Penanaman Modal Asing Terhadap Cadangan Devisa Indonesia Studi Kasus Sebalum Dan Sesudah Krisis Global - Murni Lestari, Luh Made Trisna Meita; Swara, Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 5, Mei 2016 (pp. 530-651), 2016)
Foreign exchange reserves as savings function for transactions and precautionary measures. The foreign exchange reserves can be used as the positive sentiment in the event of crisis to withhold funds. The foreign exchange reserves are not only from the current account but also capital transactions. Judging from the composition of Indonesia's foreign exchange reserves are mostly in the form of foreign exchange. After 2008, the bonds have a value that is almost the same with foreign reserves in foreign currency, meaning the influx of foreign investment is able to increase the amount of foreign exchange reserves in Indonesa. The data used is secondary data and the data were analyzed by using multiple linear regression analysis. The results of data analysis showed partial net exports, the US dollar exchange rate and FDI positive and significant impact on foreign exchange reserves. At the same time, the independent variables have significant influence amounted to 87.7% of foreign exchange reserves. foreign exchange reserves have variable value difference between before and after the global crisis significantly.
Keywords: exchange reserves, net exports, foreign exchange, FDI, global crisis